2016
DOI: 10.1093/bioinformatics/btw767
|View full text |Cite
|
Sign up to set email alerts
|

Cross-React: a new structural bioinformatics method for predicting allergen cross-reactivity

Abstract: ssnegi@utmb.edu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 73 publications
2
27
0
1
Order By: Relevance
“…The high sequence homology leads to the formation of similar folds, thus conserving the IgE binding epitopes across species. This causes a significant level of cross-reactivity with other phylogenetically related or unrelated species (29). Der f 25 caused wide cross-reactivity due to its conserved structural features with different species (30).…”
Section: Discussionmentioning
confidence: 99%
“…The high sequence homology leads to the formation of similar folds, thus conserving the IgE binding epitopes across species. This causes a significant level of cross-reactivity with other phylogenetically related or unrelated species (29). Der f 25 caused wide cross-reactivity due to its conserved structural features with different species (30).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of potential cross-reactive Cor a 2, was predicted by Cross-React server ( ), a tool that uses the epitope location and the three-dimensional structure of protein allergens [ 40 ]. A patch size (A) of 10, an area cutoff (A ) of 10, and the correlation cutoff of 0.10, were applied.…”
Section: Methodsmentioning
confidence: 99%
“…Data from previous studies have shown that epitopes with a high degree of similarity in amino acid sequences and three-dimensional structures could be recognized by cross-reaction antibodies [36]. Structural bioinformatics analysis showed cross-reactivity between allergenic proteins available with sequence identity >60% [37]. Therefore, only epitopes that showed a similarity of <60% with all other flaviviruses were considered to be specific for ZIKV and used for downstream analysis.…”
Section: Methodsmentioning
confidence: 99%